A new peculiar isometopine genus (Hemiptera: Heteroptera: Miridae) from the Eocene Baltic amber - Herczek, Aleksander; Popov, Yuri A. (Zootaxa, 2012)
This joint article should be considered as a continuation of a series of publications on fossil mirids from the Baltic amber (Prussian Formation). Miridae, or plant bugs, are the largest family of contemporary true bugs (Heteroptera) widespread all over the world, with about 1,500 genera and over 10,000 species (Schuh 1995, Kerzhner & Josifov 1999). Recent Isometopinae is a relatively small subfamily including about 190 species, strongly cryptic in habits and rare in world collections. Some are predaceous and may hunt soft-bodied, mostly aphids and scale insects. Most inclusions of fossil plant bugs are usually found in the Eocene Baltic amber, where mirids are mainly represented by the subfamilies Cylapinae, Isometopinae, and Mirinae (Popov & Herczek 2008). These fossil insects were rather scarce only in the first years of their discovery (Popov & Herczek 1992, 1993; Herczek 1993).  Judging from the described and undescribed of Baltic amber mirids known to us just now, the isometopinae are not so rare among other fossil mirids and provide evidence for a considerable diversity at least since Eocene time.